SEMIOTICS ANALYSIS OF INTERIOR OF WEST HALL OF INSTITUT TEKNOLOGI BANDUNG - Amalia, Friska (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Aula Barat Institut Teknologi Bandung or known as Barakgebouw A of Technische Hooghe School Bandung in 1920 has a magnificent form which combine Indonesian heritage vernacular typology of architecture and the Dutch’s architectural system structure. In many ways, the architect Henry Maclaine Pont speculated use the inculturation process to accommodate two cultures artefacts and caused the building has deep meaning, symbols, and culture effects with its social environment.This research will enhance the semiotics application that occur from Aula Barat Institut Teknologi Bandung as a manifest produt of inculturation using a qualitative method with grounded theory and full observation in the analysis object. In conclusion, this building includes a diachronic aspects to prove the occurance of architectural hybrid in Aula Barat Institut Teknologi Bandung